Evaluating job knowledge criterion components for use in classification research. - Zeidner J; Scholarios D; Johnson CD (Military Psychology, 2003)
In this study, we examined the potential of job knowledge tests as surrogates for hands-on criteria in the development of classification systems that use the tests of the Armed Services Vocational Aptitude Battery (McLaughlin, Rossmeisel, Wise Brandt, & Wang, 1984). Based on U.S. Army data for 15 Military Occupational Specialties, the study compared the outcomes of an assignment simulation using 2 criterion measures: one containing only job knowledge and the other containing both job knowledge and hands-on components. In this study we found comparable predictive validities for the Army operational job families and a high positive mean correlation between the 2 types of criterion in the joint predictor-criterion space. Similarities also exist in the mean predicted performance produced by the assignment simulation using each criterion measure. This outcome equivalence suggests that job knowledge measures could be useful, affordable surrogates for hands-on criteria in developing classification procedures.